Implementation of an M-commerce dropshipping model through a mobile application with augmented reality technology - Angulo Montes, Luis Enrique (2022)
This new reality has shown us that it is inevitable to migrate to a new form of trade, without borders, looking for savings at costs and prices of the product or service. Based on an exploratory-descriptive methodology, we propose to innovate when selling clothing via the web by using an augmented reality application and intelligent mannequins that allow us to assure customers that the size chosen is the correct one.